Os estágios na formação dos estudantes do ensino superior: tópicos para um debate em aberto - Susana Caires; Leandro S. Almeida (Universidade do Minho, 2000)
This article describes the different ways of organising and conceptualizing the practicum experience in Higher Education. Goals of the practicum, main competences to develop, models of supervision, assessment criteria and some of the theoretical background to these issues are discussed along the article. Despite the growing recognition of the importance of the practicum on the development of Higher Education students, the debate around this issue has not been thorough enough, as can be concluded from the scarce literature on this theme. We hope that our work can promote a more open discussion around it, a task to be undertaken not only within University but mainly by it.